The The Effect Of Work Discipline And Non-Physical Work Environment On Employee Performance In Bumi Waras District, Bandar Lampung City - Ida Jaya; Azra Akinda Kurnia (Journal Of Marketing and Technology Management, 2025)
This study was conducted to analyze the effect of work discipline and the non-physical work environment on employee performance at the Bumi Waras Sub-District Office, Bandar Lampung City. The research employed a quantitative approach using an associative method. The data used consisted of primary and secondary data. Data collection techniques included library research and field research, which involved distributing questionnaires, conducting interviews, and making observations. The population of this study comprised all employees of the Bumi Waras Sub-District Office, Bandar Lampung City, totaling 35 people. A saturated sampling technique was used, so the entire population was taken as the research sample. Data processing and analysis were carried out using the IBM SPSS 20 application. The research instrument testing included validity and reliability tests, while the data analysis prerequisite tests consisted of normality and linearity tests. The analytical methods applied were multiple linear regression analysis and the coefficient of determination test. Hypothesis testing was conducted through partial testing (t-test) and simultaneous testing (F-test). The results of the study indicate that work discipline has a positive and significant effect on employee performance, the non-physical work environment also has a positive and significant effect on employee performance, and simultaneously, work discipline and the non-physical work environment have a positive and significant effect on employee performance at the Bumi Waras Sub-District Office, Bandar Lampung City.